'Weaving lifestyle habits': Complex pathways to health for persons at risk for stroke. (17th February 2022) - Mälstam, Emelie; Asaba, Eric; Åkesson, Elisabet; Guidetti, Susanne; Patomella, Ann-Helen
Abstract: Background: It is important to understand how healthy lifestyle habits can be developed as they are essential in cardiovascular disease (CVD) prevention. There is limited knowledge regarding whether, and how, engaging occupations (things that people do and occupy themselves with) can promote and help sustain healthy lifestyle habits for persons at risk for CVDs, including stroke. Aim: The aim was to develop knowledge of how engaging in occupations can contribute to changes in lifestyle habits among persons at risk for stroke. Methods: Six adults presenting with stroke risk factors were interviewed on several occasions after participating in an occupation-focused stroke prevention programme. Grounded theory was utilised, and constant comparative methods guided the analysis. Findings: Changing lifestyle habits was perceived as a complex process, much like weaving a fabric with many parallel and interlacing threads. Literacy of both health and occupations and participation in engaging occupations were important facilitators for promoting healthy lifestyle habits, yet engagement in health-promoting occupations was described as conditioned behaviour. Conclusions: CVD prevention programmes can benefit from incorporating engaging occupations to promote healthy lifestyle habits and literacy of health and occupations. However, contextual factors conditioning health and occupations should be considered when developing and implementing sustainable interventions.